Transparent Soap from Virgin Coconut Oil with Addition of Papaya Fruit Flesh Extract - Juangga Joseph A. Marpaung; Dewi Fortuna Ayu; Raswen Efendi (JURNAL AGROINDUSTRI HALAL, 2019)
This research was aimed to get the best transparent soap from virgin coconut oil with addition of papaya fruit flesh extract.  Research method used completely randomized design (CRD) which consisted of five treatments and repeated three times.  Addition of papaya fruit extract were 10 g, 20 g, 30 g, and 40 g into 200 g soap stock.  Data were analyzed by using analysis of variance and continued with duncan’s new multiple range test at 5%.  Parameters of the transparent soap observed were chemical properties and organoleptic test.  Result of ANOVA showed that free fatty acid, free alkali, and insoluble material in ethanol had met the standard of solid soap SNI 3532-2016 except for water content and total fatty acid.  Based on this research, the best formula of transparent soap was with addition of papaya fruit flesh extract 40 g which had 29.87% moisture content, 30.46% total fatty acid, 1.06%, insoluble material in ethanol, 0.15% free fatty acid, 0% free alkali, 9.03 pH, 89.43% foam stability, and 349.55µg/ml antioxidant activity.  Sensory assessment of soap by panelist showed that the soap had an orange color, papaya scented, soft texture, and overall hedonic was a little bit liked by panelist.